2020
DOI: 10.1101/2020.03.16.979534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tau accumulates in Crohn’s disease gut

Abstract: A sizeable body of evidence has recently emerged to suggest that gastrointestinal inflammation might be involved in the development of Parkinson's disease. There is now strong epidemiological and genetical evidence linking Parkinson's disease to inflammatory bowel diseases and we recently demonstrated that the neuronal protein alpha-synuclein, which is critically involved in Parkinson's disease pathophysiology, is upregulated in inflamed segments of Crohn's colon. The microtubule associated protein tau is anot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Intracellular alpha-synuclein staining in infiltrating monocytic cells from colonic biopsies of UC and CD patients was also described in a small study [21]. The co-occurrence of alpha-synuclein and tau deposits has been described in PD [22] and further supporting pathophysiological links between PD and CD, upregulation of two main human tau isoforms has been shown in the ENS of CD patients [23]. The relationship may be genetically mediated; as discussed above, there is evidence of genetic overlap between CD and PD, both from GWAS, as well as data from LRRK2 cohort studies [8,24].…”
Section: Inflammatory Bowel Disease Irritable Bowel Syndrome and Park...mentioning
confidence: 73%
“…Intracellular alpha-synuclein staining in infiltrating monocytic cells from colonic biopsies of UC and CD patients was also described in a small study [21]. The co-occurrence of alpha-synuclein and tau deposits has been described in PD [22] and further supporting pathophysiological links between PD and CD, upregulation of two main human tau isoforms has been shown in the ENS of CD patients [23]. The relationship may be genetically mediated; as discussed above, there is evidence of genetic overlap between CD and PD, both from GWAS, as well as data from LRRK2 cohort studies [8,24].…”
Section: Inflammatory Bowel Disease Irritable Bowel Syndrome and Park...mentioning
confidence: 73%
“…Additional experiments performed in the primary culture of enteric neurons and nuclear factor erythroid 2–related factor 2 knockout mice showed that the up‐regulation of tau was not transcriptionally regulated but instead likely resulted in a decrease in protein clearance via an nuclear factor erythroid 2–related factor 2 pathway (Prigent et al. 2020), as already reported for tau in the CNS (Jo et al. 2014).…”
Section: Tau Is Up‐regulated In Crohn's Disease Gutmentioning
confidence: 77%
“…Regarding enteric neuropathies, we were unable to detect any sarkosyl‐insoluble tau in the GI tract samples from Crohn's disease cases, despite the fact that tau is up‐regulated in Crohn's disease gut (Prigent et al. 2020). We believe that the identification of potential pathological tau species in the gut would greatly benefit from the recently developed ultrasensitive amplification techniques such as protein misfolding cyclic amplification or real‐time quaking‐induced conversion (Kraus et al.…”
Section: Tau In the Gut How To Move Forward?mentioning
confidence: 88%
See 1 more Smart Citation
“…Additional candidate shared genes between PD and CD have recently come to attention. There are hints that both alpha-synuclein and tau proteins, encoded by the SNCA and MAPT genes respectively, and considered pathological hallmarks in PD, may also be involved in CD: increased expression levels of alphasynuclein protein were detected in inflamed tissues of CD patients [110] and tau protein expression was found upregulated in the enteric nervous system in CD patients [111]. However, these studies were carried out at a protein level and do not provide enough evidence to assess genetic comorbidity.…”
Section: Genetic Comorbidities Between Parkinson's Disease and Autoim...mentioning
confidence: 99%